Amylase immobilization on calcined-kaolin and sodium alginate beads - Nor Sa'adah, Mohamed (2009)
The objective of this research was to study the techniques for α-amylase immobilization on two different support materials. α-Amylase from Bacillus sp was immobilized by two different techniques which were physical adsorption onto calcined-kaolin and entrapment in sodium alginate beads. The advantages of attaching enzymes to a solid support and a few of the major reasons are single batch of enzyme can be used either multiple or repetitive and at the same time it can save cost. The immobilized α-amylase exhibited better thermostability than the free one. It is believed that kaolin and alginates has tremendous potential to be utilized as solid support material. It was estimated that the percentage of protein loading was 59% for adsorption onto calcined-kaolin, whereas for entrapment in sodium alginate, 74% of protein was immobilized. The immobilized α-amylase was tested for its capacity of converting starch into glucose, as well as its optimum pH and temperature. The optimum pH and temperature for both immobilized α-amylase were found to be pH 8 and 70°C, respectively.